EFFECT OF OZONIZATION ON COD AND BOD5 VALUES OF WASTEWATER FROM DETERGENT MANUFACTURER - Adi Mulyanto; Neni Sintawardani (Jurnal Kimia Terapan Indonesia, 1998)
The aim of this experiments were to examine the effect of ozonizotion on COD and BOD5 value of wastewater from a detergent manufacturer and to put forward the efficiency of COD and BOD5 removal as a function of the ozonization. It has been known that the detergent industry produces wastewater with high concentration of both COD and BOD5. The observation showed that the ozonization alone was not a practical approachfor COD and BOD5 removal. However, the role of ozonization as a preliminary process before the biological one seems to be significant.